Mistakes in acanthamoeba keratitis diagnosis - Дрожжина, Галина Іванівна; Іванова, Ольга Миколаївна; Середа, Катерина Віталіївна (My University, 2024)
Purpose - to present a clinical case of acanthamoeba keratitis misdiagnosis in a patient who is contact lenses wearer Setting State Institution «The Filatov Institute of eye diseases and tissue therapy NAMS of Ukraine», Odessa, Ukraine Report of case Patient, 60 y.o, complained of photophobia, lacrimation, pain in the left eye. Patient used contact lenses for 15 years. 6 months ago, she took thermal baths and a week later noticed inflammation in her eye. For 2.5 months patient was treated for herpetic keratitis. Due to the lack of positive dynamics, she turned to a private medical center, where during bacterioscopic examination of conjunctival smear acanthamoeba trophozoites were detected. Patient was prescribed voriconazole, chlorhexidine, moxifloxacin, dexamethasone, dexpanthenol. Two-time cryoapplication of the affected area of the cornea was performed.. In 3 weeks after cooling down patient was diagnosed with central corneal ulcer with stromal thinning. Microscopy of a scraping from the eye revealed trophozoites of acanthamoeba. Upon admission to our hospital (6 months from the disease onset): conjunctiva is hyperemic, paracentral corneal ulcer 6.5 mm with heterogeneous infiltration, thinning in the center and a ring-shaped infiltrat е. The anterior chamber is of medium depth, pupil is round, cataract. BCVA of the left eye 0.01. The results of microbiological examination of conjunctival cavity revealed epidermal staphylococcus and yeast-like fungi. Corneal confocal microscopy performed no pathognomonic changes for trophozoites or acanthomeba cysts. She was diagnosed with corneal ulcer of mixed etiology (bacterial-fungal, acanthomebic?) and treated with chlorhexidine 0.04%, fortified gentamicin and voriconazole, brolen. Left eye underwent penetrating keratoplasty with a diameter of 7.0/7.5 mm. Microbiological study of the corneal disc removed during surgery, conducted in two independent laboratories no fungal, gram-positive and gram-negative microorganisms, as well as microsporidium or acanthamoeba was founded. In the postoperative period, microflora growth was not detected in cultures from the conjunctiva. At discharge from the hospital, the graft was transparent and the surface was epithelialized, cataract. Intraocular pressure was normal. BCVA OS = 0.06. After 6 months phacoemulsification+IOL was performed. BCVA = 0,5. Conclusion/Take home message A significant number of acanthamoeba keratitis diagnoses are based on clinical signs and confocal microscopy data. Analysis of the results of conjunctival smear and scrapings from the cornea require an experienced examiner. Careful investigation of anamnesis, clinical symptoms as well as knowledge of the differential diagnostic of the disease and adequate assessment of the prescribed treatment effectiveness can help to make the correct diagnosis on time.